Pendampingan Interpretasi dalam Pengelolaan Komponen Wisata Komunitas Desa Wisata Lantebung, Makassar: Interpretation Assistance in the Management of the Community Tourism Component of Lantebung Tourism Village, Makassar - Djabbar, Atriana; Susanto, Yenny (PADAIDI: Journal of Tourism Dedication, 2024)
This study aims to evaluate community service activities in the management of tourist destinations in Lantebung Village. The focus of this research is to assess the effectiveness of the community service activities conducted in enhancing the community's capacity to manage tourism. Based on a survey of 30 respondents, the results show that the majority of the community feels involved in the management of the tourist destination (70%) and agrees with the clear division of roles (83.33%). However, some respondents feel that their involvement is still limited. Additionally, 100% of respondents acknowledge the need for increased community participation in tourism activities. The mentoring program provided has been perceived as beneficial, although some respondents feel its impact has not been fully maximized. This study recommends that community service activities focus on improving the division of roles, enhancing communication, and strengthening managerial and tourism marketing capacity to optimize the impact on the community.